Pengaruh Green Brand Positioning Terhadap Green Repurchase Intention Melalui Attitude Toward Green Brand (Studi Pada The Body Shop Di Kota Bandung) : (Studi Pada The Body Shop Di Kota Bandung) - Pambudi, Zidan Basyarahil Rais; Dewi, Citra Kusuma (eProceedings of Management, 2024)
Environmental issues are now a concern in various industrial sectors, especially related to plastic waste. Thecosmetics and skincare industry is one of the biggest contributors. The Body Shop is one of the cosmetic andskincare brands that cares about environmental sustainability by creating environmentally friendly products. TheBody Shop is active in campaigning for environmental issues by producing environmentally friendly, natural-basedgoods. This study aims to determine the extent of the influence of green brand positioning on green repurchaseintention through attitudes towards green brands among The Body Shop consumers in Bandung City. This studyuses a quantitative method that includes various tests such as validity, reliability, and hypothesis testing. The samplewas selected using a non-probability sampling method with a purposive sampling strategy. The respondents of thisstudy were The Body Shop customers who live in Bandung City and have purchased The Body Shop products before,with a total of 108 samples. The results of the study showed that the Green Brand Positioning variable has apositive and significant influence on the Attitude Toward Green Brand variable. In addition, the Attitude TowardGreen Brand variable also has a positive and significant influence on the Green Repurchase Intention variable. TheGreen Brand Positioning variable was also proven to have a positive and significant influence on the GreenRepurchase Intention variable.Keywords-green marketing, green brand positioning, attitude toward green brand, green repurchase intention